2015
DOI: 10.1016/j.ejcdt.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive positive pressure ventilation and exercise training in patients with stable hypercapnic chronic obstructive pulmonary disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a disease with progressive course of dyspnea which leads to reduced health related quality of life (HRQoL). Exercise training has useful effects toward their exercise tolerance and health related quality of life (HRQoL). However extreme breathlessness limits these patients in maintaining exercise training. Non-invasive positive pressure ventilation (NIPPV) is considered a beneficial treatment option for chronic stable hypercapnic respiratory failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Contrary to these results, Rooyackers et al [ 51 ] and Wadell et al [ 52 ] claimed no statistically significant change in O 2 saturation and PaCO 2 between the O 2 -trained group and control group, so they reported no additional benefit for super-added oxygen in PR concerning oxygen saturation. Moreover, Cui et al [ 53 ] and Gad et al [ 45 ], in their studies of the role the NIV in PR, showed improvement in spirometric measures, arterial blood gas, dyspnea and QoL in stable hypercapnic COPD patients with significant decrease of PaCO 2 in the NPPV group than (exercise only) group, so it matched with our results. Also, Garrod et al [ 54 ] reported a small improvement in arterial oxygenation in the (NPPV) group in comparison with the (exercise only) group, but with a significant difference between both groups, they explained the increase in PaO 2 in these patients by the improvement in alveolar ventilation and reduced hyperinflation but they stated no significant difference in PaCO 2 after ending their study in both groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Contrary to these results, Rooyackers et al [ 51 ] and Wadell et al [ 52 ] claimed no statistically significant change in O 2 saturation and PaCO 2 between the O 2 -trained group and control group, so they reported no additional benefit for super-added oxygen in PR concerning oxygen saturation. Moreover, Cui et al [ 53 ] and Gad et al [ 45 ], in their studies of the role the NIV in PR, showed improvement in spirometric measures, arterial blood gas, dyspnea and QoL in stable hypercapnic COPD patients with significant decrease of PaCO 2 in the NPPV group than (exercise only) group, so it matched with our results. Also, Garrod et al [ 54 ] reported a small improvement in arterial oxygenation in the (NPPV) group in comparison with the (exercise only) group, but with a significant difference between both groups, they explained the increase in PaO 2 in these patients by the improvement in alveolar ventilation and reduced hyperinflation but they stated no significant difference in PaCO 2 after ending their study in both groups.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to the present study’s results, Spielmanns et al [ 33 ] noticed no improvement in lung functions in both groups (air-trained and oxygen-trained group) at the end of the PR programme, suggesting that airway obstruction was a permanent cause of exercise limitation. Fakharian et al [ 41 ] and Gad et al [ 45 ] demonstrated improvement in FEV1 and FVC values after the sessions in both groups (PR group and NIV+PR group). However, Duiverman et al [ 46 ] found a more significant improvement in FEV1 in (NIV+PR) than in the PR alone group.…”
Section: Discussionmentioning
confidence: 99%
“…6,7, We included 21 RCTs 6,17,19,20,[23][24][25][26][27][28]30,33,34,[36][37][38][39]41,43,46,48 and 12 observational studies. 18,21,22,29,31,32,35,40,42,44,45,47 These studies were conducted in the United States (n = 4), Canada (n = 1), Europe (n = 23), Asia (n = 3), Africa (n = 1), and Australia (n = 1). All included studies enrolled patients in the home setting, and no studies enrolled patients in assisted living settings.…”
Section: Resultsmentioning
confidence: 99%
“…An additional 83 citations were identified through reference searching and gray literature search (eFigure in Supplement 2). We included 33 studies (34 articles) evaluating 51 085 patients (mean [SD] age, 65.7 [2.1] years; 43% women) . We included 21 RCTs and 12 observational studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation